Conflict Of Interest In Philippa Gregory's The White Queen (2009): A Marxist Literary Criticism - Wahyuningtyas, Putri Ika; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This research paper is primarily intended to identify how the conflict of interest in Philippa Gregory's The White Queen viewed from Marxist's perspective, and to analyze the novel based on its structural elements. In analyzing the novel, the writer uses qualitative study. The data are collected by using two kinds of techniques: documentation and library research. The technique of data analysis is descriptive analysis. The research significance is to give contribution to the body of knowledge, particularly the literary study on Philippa Gregory's The White Queen. The result of analysis confirms, first, based on the analysis it is clear that there is a close relation between this novel and the social reality in England in early twenty first century. Second, Gegory wants to explain the conflict of interest oriented from vested interest to human in the society of England in early of twenty first century through 'The White Queen' novel.